CAMBODIAN TEACHERS' READINESS OF USING ICT: THE CASE OF RURAL UPPER-SECONDARY SCHOOLS - Sina Pang; Ravy Nhor; Sereyrath Em (Jurnal As-Salam, 2022)
Many people in the twenty-first century are familiar with technology. The Education? Ministry of the Kingdom of Cambodia has also included ICT subjects in the school curriculum. However, due to the lack of preparation, many Cambodian teachers, especially those living in the countryside, face many challenges with ICT applications and seem unprepared to use ICT in their teaching. The current study employed a quantitative method through survey techniques. It aimed to examine Cambodian teachers' perceptions of ICT use in the classroom, the level of training on ICT, and the challenges of technical support and ICT infrastructure in schools. 109 teachers (25 females) were asked to participate in the study. The results show that all the teachers had a positive attitude toward using ICT in teaching. Although most of them are confident in their ability to use ICT, less than half use it in their teaching. The result also shows that most teachers received training on using ICT, but they possessed only basic computer skills. Most of them reported that having poor access to computers and the internet was their main challenge. Future studies should be conducted using a qualitative or mixed-methods design with similar topics. The study regarding the challenges of implementing an ICT school curriculum provided by MoEYS is also recommended.